Constitutional Inquiry Rights in Evaluating Constitutional Court Decisions: A Case Study of MK Decision No. 90/PUU-XXI/2023: Hak Angket Konstitusi dalam Mengevaluasi Putusan Mahkamah Konstitusi: Studi Kasus Putusan MK No. 90/PUU-XXI/2023 - Razak, Askari; Amin, Fakhry (Rechtsidee, 2023)
This research focuses on analyzing the construction of the parliamentary inquiry right (hak angket) within the context of the controversial Constitutional Court (Mahkamah Konstitusi, MK) Decision No. 90/PUU-XXI/2023 in Indonesia. The decision, which interprets the age requirement for presidential and vice-presidential candidates, has sparked debates about the potential misuse of MK's authority. The study aims to understand the legal construction of the DPR’s parliamentary inquiry in light of the 1945 Constitution and relevant legislations, and to assess its implications on the oversight function of representative institutions. Employing a normative legal research methodology, the study analyzed legislation, legal concepts, and conducted expert interviews and content analysis. The findings reveal that the parliamentary inquiry, as a constitutional right of the DPR stipulated in Article 20A paragraph (2) of the 1945 Constitution, is utilized to assess the impact of MK Decision No. 90/PUU-XXI/2023 on Indonesia’s democracy and electoral system. The study highlights the need for DPR to observe legal provisions and ensure transparency and accountability in its inquiry process, emphasizing the significance of balancing democratic principles, transparency, and protection of citizens’ political rights in the oversight mechanism.Highlights: Parliamentary Inquiry and Democracy: Exploration of the DPR's inquiry right in relation to MK's decision, emphasizing its importance for democratic accountability. Legal and Democratic Implications: Focus on the legal boundaries and democratic significance of applying the inquiry to a judicial decision. Transparency and Accountability: Highlighting the need for transparency and accountability in the parliamentary inquiry process. Keywords: Parliamentary Inquiry, Constitutional Court Decision, Legal Analysis, Indonesian Democracy, Oversight Function